Northeast Asian Allorhynchium van der Vecht (Hymenoptera: Vespidae), with a key to Oriental species - Tan, Jiang-Li; Achterberg, Cornelis Van; He, Yi-Fei; Carpenter, James M. (Zootaxa, 2018)
The Oriental species of Allorhynchium van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) are keyed for the first time and their distribution is summarised, with special reference to China and Vietnam. Archancistrocerus Giordani Soika, 1986, is synonymized with Allorhynchium van der Vecht (syn. nov.). Allorhynchium diffinis (Giordani Soika, 1986) is a new combination and A. quadrimaculatum Gusenleitner, 1997, is recorded from Vietnam for the first time.